Antimicrobial stewardship programs in emergency departments: how do we measure antimicrobial use? A systematic review. - Ruiz-Ramos, Jesus; Vallvé Alcón, Emili; Moreno Ramos, Francisco; Santolaya-Perrín, Rosario; Guardiola Tey, Jose María (Revista Española de Quimioterapia, 2021)
Objectives. The implementation of antimicrobial stewardship programs (ASPs) has become a usual practice in hospital settings. However, the method for monitoring antimicrobial use in accident and emergency departments (ED) is not yet adequately defined. Thus, the objective of this review is to describe antimicrobial use indicators used by ASPs implemented in ED. Material and methods. A systematic review was performed based on studies found in the following academic research databases: MEDLINE, EMBASE, Web of Science, and Scopus (Period: January 2000 to December 2019). Controlled clinical trials, before-and-after studies, interrupted time series, and repeated measures studies assessing the impact of ASPs on antimicrobial use in ED were included; studies published in languages other than English or Spanish were excluded from this review. Results. Twenty-six studies met the inclusion criteria and were included in this systematic review. In total, 15 (62.5%) studies described the ASP team members who collaborated with the ED staff. Most (21; 80.8%) studies used the percentage of patients with an antibiotic prescription as an indicator. Four (15.4%) studies included defined daily dose data. The antibiotic treatment duration was reported in four (15.4%) studies. Only two studies assessed the impact of the ASP using microbiological indicators, both of which used the incidence of infection with Clostridioides difficile as the indicator. Conclusions. The reports of experiences in implementing ASPs in ED show heterogeneous antimicrobial use indicators, which makes it difficult to compare results. Therefore, antimicrobial use indicators for ASPs must be standardised between hospital units.